2009
DOI: 10.1592/phco.29.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic‐Induced Hyperprolactinemia

Abstract: Use of antipsychotic agents has been associated with hyperprolactinemia, or elevated prolactin levels; this hormonal abnormality can interfere with the functioning of reproductive, endocrine, and metabolic systems. As antipsychotic agents are increasingly used for both United States Food and Drug Administration-approved and nonapproved indications, many individuals are at risk for developing antipsychotic-induced hyperprolactinemia. First-generation antipsychotics pose the greatest risk of causing this adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
135
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 55 publications
1
135
1
8
Order By: Relevance
“…Enhanced 5-HT bioactivity leading to local PTHrP secretion may be one mechanism involved in bone loss caused by these drugs. In addition, antidepressant and antipsychotic drugs tend to cause hyperprolactinemia, and the degree of hyperprolactinemia can be substantial (4,33). Demineralization of the bones is also commonly associated with hyperprolactinemia resulting from prolactinomas (12,27,44,48).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced 5-HT bioactivity leading to local PTHrP secretion may be one mechanism involved in bone loss caused by these drugs. In addition, antidepressant and antipsychotic drugs tend to cause hyperprolactinemia, and the degree of hyperprolactinemia can be substantial (4,33). Demineralization of the bones is also commonly associated with hyperprolactinemia resulting from prolactinomas (12,27,44,48).…”
Section: Discussionmentioning
confidence: 99%
“…Bostwick et al reported that if the effects of PRL are evident, the drug can be changed to another agent that is less likely to affect PRL levels. 17) Further research is needed to clarify the appropriate method for PRL monitoring. In the present study, using ROC curve analysis, we estimated that the cutoff value of PRL that can lead to adverse side effects induced by antipsychotic drugs, such as menstrual disorders, was 60 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…9 One treatment option is reducing the dose of the antipsychotic but some do not recommend this as first-line treatment as this may reduce therapeutic efficacy and may also fail to reduce prolactin levels sufficiently. 4,10 The literature generally suggests that the first step in active management would be to switch to an antipsychotic not associated with prolactin elevation. [2][3][4]7,9,10 For some patients, however, switching drugs is not an option, for example, for those on a depot preparation where compliance is an issue or in patients in whom the risk of relapse is too great.…”
Section: Discussionmentioning
confidence: 99%